EXPERIENCE IN THE USE OF ACETYLCYSTEINE IN THE TREATMENT OF RESPIRATORY INFECTIONS IN YOUNG CHILDREN - I. V. Davydova; T. V. Tourte; L. S. Namazova-Baranova; A. Yu. Simonova; L. R. Tarasova; V. V. Altunin (Педиатрическая фармакология)
Treatment of respiratory infections in early childhood requires extensive use of direct action mucolytic drugs, which include derivatives of acetylcysteine. However, data on efficacy and safety of acetylcysteine in the treatment of both acute and chronic bronchopulmonary diseases in children during the first two years of life are few and contradictory. The article contains the authоrs’ data on the use of granular acetylcysteine for the syrup preparation in the treatment of young children.